A simple feedback control for a chaotic oscillator with limited power supply - de Souza, S. L. T.; Caldas, I. L.; Viana, R. L.; Balthazar, José Manoel [UNESP]; Brasil, R. M L R F (Elsevier B.V., 2007)
We proposed a simple feedback control method to suppress chaotic behavior in oscillators with limited power supply. The small-amplitude controlling signal is applied directly to the power supply system, so as to alter the characteristic curve of the driving motor. Numerical results are presented showing the method efficiency for a wide range of control parameters. Moreover, we have found that, for some parameters, this kind of control may introduce coexisting periodic attractors with complex basins of attraction and, therefore, serious problems with predictability of the final state the system will asymptote to. (c) 2006 Elsevier Ltd. All rights reserved.